Sumbangan Kor Agama Angkatan Tentera (KAGAT) dalam aktiviti keagamaan : kajian dalam Batalion ke-12 RAMD / Tirmizi bin Hj Md Isa - Hj Md Isa, Tirmizi (2011)
The Contribution of Armed Forces Religious Corps (KAGAT) in Religious Activities: A Study On 21st Battalion Royal Malay Regiment. A dissertation for the Department of history and Islamic Studies, University of Malaya, Kuala Lumpur 2004. This study intends to evaluate and investigate the contributions of Forces Religious Corps (KAGAT) in religious activities. The reason is that is there are those who are still unconvinced of the contributions by KAGAT in ATM. This study will elucidate efforts and involvement of KAGAT in carrying out religious activities in 21st RMR. This research applies two methods which are library research where data are collected from various resources such as books, magazines and the internet, while the second method is field work, divided into three methods; survey, interview with the officials and lastly observations by the writer. This study will also present results from the analysis of the survey forms that were distributed to 240 respondents in the 21st RMR that include various levels; 20 questions for the officers, 180 for the members LLP, 20 for the members of the BAKAT or wives of the members and 20 questions for the children of the members of the battalion. The result of this study shows that the KAGAT’s contributions started along with the establishment of Malaysia military service and its foundation was indeed a necessity. KAGAT is acknowledged as successful in playing its part in performing religious activities. Its position in delivering da’wah mission as well as Islamic knowledge and religious services to members of ATM cannot be denied. This study ends with a number of proposals and suggestions in order to find the best solution towards more effective religious activities.